Reducing the Costs and Enhancing the Benefits of Formality : From the Firm's Perspective - Ruppert Bulmer, Elizabeth; Kuddo, Arvo; Weber, Michael (World Bank, Washington, DC, 2017)
The high incidence of informality in developing countries acts as a drag on economic development due to the associated efficiency and equity costs and implied weak governance. Policy makers therefore want to reduce informality. This note presents guidance on policy levers to make formality more attractive and informality less attractive from the perspective of small, medium and large firms, and from the perspective of micro-entrepreneurs. It elaborates the challenges for shifting incentives in favor of being formal and employing workers on formal contracts rather than operating under the regulatory radar, and presents a range of policy options.